Chest wall stabilization and rib fixation using a nitinol screwless system in selected patients after blunt trauma: Long-term results in a single-center experience. (28th May 2021) - Hojski, A; Xhambazi, A; Wiese, M; Subotic, D; Bachmann, H; Lardinois, D
Abstract: Objective: First experience with rib fixation by use of nitinol in terms of reliability, morbidity, influence on pain control and quality of life in a large series of selected patients after blunt chest trauma. Methods: Data of all patients who underwent rib fixation by use of nitinol were retrospectively analyzed in terms of indications, morbidity and in-hospital mortality. Standard clinical and radiological follow-up was performed at 1, 3, 6, 12 months after discharge. Short-, mid- and long-term pain status and health related quality of life (HRQOL) were assessed using visual analogous scale (VAS) and short form 12 (SF-12) questionnaire. Results: From September 2017 until April 2019, 70 patients underwent rib fixation by use of the nitinol device, consisting of dislocated and painful fractures (67.1%), pseudarthrosis (15.7%), emergencies with hemodynamical instability (8.6%), and flail chest (8.6%). Morbidity was 21.4% without wound infection; in-hospital mortality was 2.9%. Fracture of the material occurred in 5.7% of the patients during the first year but removal of the material was not necessary. Analysis of the pain score showed a decrease of the pain with a statistical significance for the whole collective and in the group with series of dislocated fractures (p < 0.001, linear mixed-effects models). Assessment of HRQOL revealed a significant improvement of the physical and mental score for the mid- and long-term analysis. Conclusion: Our results suggest that rib fixation with nitinol device is reliable, associated with an acceptable morbidity, and significantly decreases pain and improves health related quality of life.